(untitled) (Modern American Journal of Biological and Environmental Sciences, 2025)
The article explores the scientific and pedagogical foundations of integrating medical biology and pedagogy in the process of personality development. It emphasizes the interdisciplinary approach that combines biological principles of human growth and pedagogical strategies aimed at shaping students’ intellectual, moral, and emotional spheres. The integration model proposed in the study contributes to forming holistic professional competence among future medical specialists. The research highlights the importance of biopedagogical thinking, ethical reflection, and innovation in medical education for the sustainable development of the individual and society.